Readers theatre something old but still an assiduous tool to acquire english language / Alice Shanthi...[et al.] - Shanthi, Alice; Jaafar, Zuraida (Universiti Teknologi MARA, Kedah, 2020)
The study was carried out to investigate the effects of including readers’ theatre (RT) as part of classroom instruction in English proficiency classes. The participants for the study were first-semester diploma students who had enrolled in English language proficiency class at a public university. A sample of 85 first semester diploma students was purposively chosen to represent the participants for treated and control groups respectively. Readers’ theatre was added to the experimental group’s proficiency class, while the control group was taught the language skills without readers theatre. At the end of the study the students were tested in three different language skills; speaking (role play), listening and reading (reading comprehension). Data was analyzed using a quantitative analytical tool SPSS. The results indicated the mean score of speaking, listening and reading for the treated group students were higher than the control group students. Next, independent T-tests at a 0.05 level of significance showed that there was a significant difference on mean test score between the treated and controlled group for speaking, listening and reading tests where all the p-values were less than 0.05. The results invoke that the use of RT in classroom instruction improves the students’ test score in speaking, listening, and reading in English. Hence, incorporating Reader’s Theatre in teaching and learning of the English language is beneficial to increase fluency skill for the tertiary students.